PENGERINGAN BIJI KAKAO MENGGUNAKAN PLASTIK ULTRAVIOLET DAN PENENTUAN MUTU SESUAI STANDAR SNI - Ansharullah, Ansharullah; Tamrin, Tamrin; Wahyuni, SrI; La Rianda, La Rianda; Madiki, Abdul; Bahrun, Andi; Iswandi, Marsuki; Nafiu, La Ode; La Aba, La Aba; Salam, Nur (Jurnal Abdi Insani, 2023)
abstract